Jabatan Kerja Raya Johor Tender Management System - Muhammad Haziq Rifqi Hassan,; Muhaini Othman, (Applied Information Technology And Computer Science, 2023)
Abstract:  The Tender Management System is designed to efficiently handle tender management tasks. Its development was motivated by the need to address issues arising from manual system usage. The proposed solution involves creating a web-based system that offers user-friendly features. To achieve this, an agile development model was adopted. MySQL software serves as the database, while Hypertext Markup Language (HTML) and Hypertext Preprocessor (PHP) are utilized as the programming languages. The system undergoes iterative development based on the chosen model, ensuring it aligns with the customer's requirements. Primarily, the system aids administrators, tendering staff, and companies in managing the tender process by providing online access to tender documents. The aim is to enhance efficiency and effectiveness in tender management at Jabatan Kerja Raya Johor. Keywords: Tender Management System, Web-based system, Agile development model